Novel Geometric Morphometric (GMM) Application to the Study of Bronze Age Tutuli - Christina Vestergaard; Christian Steven Hoggard (Danish Journal of Archaeology, 2019)
In this paper, we examine the morphological diversity of the tutuli object group from the earlier Nordic Bronze Age (henceforth NBA) – an often over-looked object group despite their abundance specially, temporally and contextually. Currently, only a few studies of the morphological diversity of tutuli have been published, and these consist primarily of decade-old-typologies. The objective of this of this paper is first and foremost methodological, as we examine two research questions – concerning classification and periodisation – through a novel two-dimensional geometric morphometric (henceforth GMM) framework and subsequent multivariate analysis. Inherently we examine whether specific shapes conform to the classificatory of the Montelius typology, and whether a temporal relationship exists between types and shapes.